Teknik Pemeriksaan CT Scan Abdomen Pada Kasus Tumor Intra Abdomen Di Instalasi Radiologi Rumah Sakit X - Dewi Rahmawati; Anak Agung Aris Diartama; Rahmat Widodo (Lembaga Pengembangan Kinerja Dosen, 2024)
CT-Scan (Computed Tomography Scanner) is a diagnostic support tool that has universal application for examining all body organs, such as the central nervous system, muscles and bones, throat and abdominal cavity. CT-Scan (Computed Tomography Scanner) was first used in early 1970s for medical diagnosis. This diagnostic technique is carried out by passing a collimated X-ray beam (±2 mm wide) over the patient's body and the radiation beam is captured by a detector system. The X-ray source and detector move in a plane around the patient's body.